2004
DOI: 10.1124/mol.65.3.675
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of the Action of Disulfiram as a Modulator of the Multidrug Resistance-Linked ATP Binding Cassette Transporters MDR1 (ABCB1) and MRP1 (ABCC1)

Abstract: The overexpression of multidrug resistance protein 1 (MDR1) and multidrug resistance protein 1 (MRP1) gene products is a major cause of multidrug resistance in cancer cells. A recent study suggested that disulfiram, a drug used to treat alcoholism, might act as a modulator of P-glycoprotein. In this study, we investigated the molecular and chemical basis of disulfiram as a multidrug resistance modulator. We demonstrate that in intact cells, disulfiram reverses either MDR1-or MRP1-mediated efflux of fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 31 publications
5
56
0
Order By: Relevance
“…Other reported mechanisms of action of disulfiram, including inhibition of P-glycoproteins involved in drug efflux and proteasome inhibition, are seen at relatively higher disulfiram concentrations (37,38). However, our findings indicating complete inhibition of phospho-MET in MKN-45 and GTL-16 DTPs (Supplementary Fig.…”
Section: Rosmentioning
confidence: 49%
“…Other reported mechanisms of action of disulfiram, including inhibition of P-glycoproteins involved in drug efflux and proteasome inhibition, are seen at relatively higher disulfiram concentrations (37,38). However, our findings indicating complete inhibition of phospho-MET in MKN-45 and GTL-16 DTPs (Supplementary Fig.…”
Section: Rosmentioning
confidence: 49%
“…2C, during 60-minute incubation, curcumin I is not metabolized, indicating that the curcumin I itself interferes with the binding of the transport substrate. Taken together, the transport and the photolabeling assay clearly showed that curcuminoids inhibit the binding of the substrates to the transporter and prevent efflux of We reported earlier that that compounds, such as disulfiram, interact with both the ATP-binding site and the substrate-binding site of ABCB1 (36). Therefore, the effect of curcuminoids on the binding of [a-…”
Section: Effect Of Curcuminoids On Atp Hydrolysis By Abcg2mentioning
confidence: 89%
“…Photoaffinity ]azidopine into the ABCG2 band was quantified by estimating the radioactivity incorporated into the band using the STORM 860 PhosphorImager System (Molecular Dynamics, Sunnyvale, CA) and the software ImageQuant as described (36). 6 cells.…”
Section: Isolation Of Crude Membranes From Abcg2-expressing Hek293 Ormentioning
confidence: 99%
“…Samples were separated on a 7% Tris-acetate gel at constant voltage, and gels were dried and exposed to X-ray film for 12 to 24 h at Ϫ80°C. The incorporation of [ 125 I]IAAP into the ABCG2 or P-gp band was quantified using the STORM 860 PhosphorImager system (GE Healthcare, Little Chalfont, Buckinghamshire, UK) and the software ImageQuaNT (GE Healthcare), as described previously (Sauna et al, 2004).…”
Section: Methodsmentioning
confidence: 99%